Growth inhibition of phytoplankton communities collected from Hoan Kiem lake by different solvent extracts Eupatorium fortune Turcz - Thuy, Duong Thi; Cuong, Ho Tu; Phuong Quynh, Le Thi; Dat, Nguyen Tien; Nga, Pham Thanh; Nguyet, Vu Thi; Kim, Dang Dinh (Academia Journal of Biology, 2015)
The objective of our study was to test the effect of two aqueous extracts, ethyl acetate and water, from Eupatorium fortune Turcz on growth of the phytoplankton community and Microcystis population collected from the Hoan Kiem lake. The results showed that the significant inhibition of phytoplankton and Microcystis cell density were observed when using ethyl acetate extract from Eupatorium fortune at concentration of 500 mg/L after 14 days of exposure. The ethyl acetate extract has the same effect as CuSO4 at 2 mg/L on the growth of Microcystis population in Hoan Kiem Lake, that 34.5% of the population was inhibited.